A critical review of the Ecological Consciousness and human needs in Alice Oswald’s poetry: An exploration of environmental sustainability in modern English verse - Alhomoud, Ghassan Nawaf Jaber; Ismail, Sayed M. (Research Journal in Advanced Humanities, 2025)
Ecological Consciousness is clearly articulated in the poetry of Alice Oswald as she uses the poetic language to address the environmental and ecological concerns. The present paper argues that the poetry of Alice Oswald serves as a vital, imaginative counterpart to the pragmatic frameworks of the UN Sustainable Development Goals (SDGs). Through a close reading of her poetry including Dart, Nobody, and Weeds and Wild Flowers, this analysis demonstrates how Oswald’s verse highlights several aspects environmental Sustainability, Human Health, the provision of Basic Needs, a critique of Energy & Industrial Leadership, and a reimagining of Future Economics. Oswald's work transcends conventional nature poetry by establishing an ecological awareness that blurs the distinction between human and non-human, prompting a significant reassessment of our role within a living, interrelated system. This study asserts that the humanities, especially poetry, are vital for cultivating the profound, sympathetic comprehension necessary to attain the Sustainable Development Goals, rendering Oswald's work not only artistic but a crucial instrument for ecological and social transformation.